2019
DOI: 10.1111/jeb.13572
|View full text |Cite
|
Sign up to set email alerts
|

Egg load is a cue for offspring sex ratio adjustment in a fig‐pollinating wasp with male‐eggs‐first sex allocation

Abstract: Fig‐pollinating wasps (Agaonidae) only reproduce within fig tree inflorescences (figs). Agaonid offspring sex ratios are usually female‐biased and often concur with local mate competition theory (LMC). LMC predicts less female‐bias when several foundresses reproduce in a fig due to reduced relatedness among intra‐sexually competing male offspring. Clutch size, the offspring produced by each foundress, is a strong predictor of agaonid sex ratios and correlates negatively with foundress number. However, clutch s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…If it is the former, it should be considered an adaptation; if the latter, it is an exaptation from the viewpoint of sex ratio adjustment. Even if laying sons first is an exaptation, the number of sons laid first could be a quantity that selection has optimized to obtain an optimal sex ratio [30,38,41] (but see [57]). The predictions of these models are similar to standard LMC models [38,41] because the same selective pressures (reduced competition between brothers [7], relatedness asymmetries [17] and more mating opportunities to brothers [13]) influence the process.…”
Section: Discussionmentioning
confidence: 99%
“…If it is the former, it should be considered an adaptation; if the latter, it is an exaptation from the viewpoint of sex ratio adjustment. Even if laying sons first is an exaptation, the number of sons laid first could be a quantity that selection has optimized to obtain an optimal sex ratio [30,38,41] (but see [57]). The predictions of these models are similar to standard LMC models [38,41] because the same selective pressures (reduced competition between brothers [7], relatedness asymmetries [17] and more mating opportunities to brothers [13]) influence the process.…”
Section: Discussionmentioning
confidence: 99%
“…That may be because under the circumstance of a longer interval, the second one will not be able to lay her full egg load due to oviposition site limitation or the loss of receptivity. Furthermore, fig wasps first lay a set number of male eggs and then female eggs, or at least mainly male eggs initially [14,39]. We infer that oviposition site limitation would be the reason for sex ratio increasing rather than that the second foundress can perceive the existence of the first foundress according to previous studies [42], so the later foundress probably cannot access the full capacity of oviposition due to the age of female flower changing.…”
Section: Discussionmentioning
confidence: 70%
“…Even so, our study corroborated the findings on another Ceratosolen species and another non-fig wasp that males die more easily [37,38] In this study, we also demonstrated the effect of host quality on offspring sex ratio from another perspective by introducing the foundresses that were pollen-loaded or pollen-free. Previous studies have suggested that active pollinators efficiently fertilize flowers in which they oviposit, and wasps' larvae feed on the nucellar tissue of normally double-pollinated flowers; thus, a lack of pollination increases larval mortality [6,39], and active pollination has probably evolved as a way to improve progeny nourishment [29,40,41]. This idea is supported by larger broods in pollinated F. hispida [31].…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al [97] introduced another technique. They removed Ceratosolen fusciceps foundresses from figs they entered and let them enter new figs in a species where females do not naturally re-enter figs.…”
Section: Approaches To Study Fig Wasp Sex Ratiosmentioning
confidence: 99%